2017
DOI: 10.1016/j.cell.2017.05.045
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic RNA Modifications in Gene Expression Regulation

Abstract: Over one hundred types of chemical modifications have been identified in cellular RNAs. While the 5’ cap modification and the poly(A) tail of eukaryotic messenger RNA play key roles in regulation, internal modifications are gaining attention for their roles in mRNA metabolism. The most abundant internal modification is N6-methyladenosine (m6A), and identification of proteins that install, recognize, and remove this and other marks have revealed roles for mRNA modification in nearly every aspect of the mRNA lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

40
2,401
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 2,477 publications
(2,645 citation statements)
references
References 150 publications
40
2,401
2
2
Order By: Relevance
“…Cold Spring Harbor Laboratory Press on May 7, 2018 -Published by rnajournal.cshlp.org Downloaded from in some quarters to be established as fact (Wang and He 2014;Fu et al 2014;Cao et al 2016;Dominissini et al 2016;Gilbert et al 2016;Roundtree et al 2017). …”
Section: Role and Cellular Location Of Other Demethylationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cold Spring Harbor Laboratory Press on May 7, 2018 -Published by rnajournal.cshlp.org Downloaded from in some quarters to be established as fact (Wang and He 2014;Fu et al 2014;Cao et al 2016;Dominissini et al 2016;Gilbert et al 2016;Roundtree et al 2017). …”
Section: Role and Cellular Location Of Other Demethylationsmentioning
confidence: 99%
“…Producing eukaryotic mRNA, especially in animal cells, requires many biochemical steps including 5ʹ capping, 3ʹ polyadenylation, obligatory and alternative splicing of many exons and base modifications, the latter of which which has been much discussed recently with respect to N6 adenosine methylation of residues that exist in mRNA (He 2010;Fu et al 2014;Wang and He 2014;Cao et al 2016;Ke et al 2017;Meyer and Jaffrey 2017;Roundtree et al 2017). To reflect more directly on the recent mRNA methylation studies and commentaries, a look back at earlier and recent techniques and conclusions is in order.…”
mentioning
confidence: 99%
“…Early studies on the abundant RNAs such as rRNA, snRNA, and tRNA demonstrated that this diversity of modifications leads to additional cellular functions for different RNA species (1). For example, rRNA modifications affect translation accuracy and efficiency and likely facilitate ribosome biogenesis.…”
mentioning
confidence: 99%
“…3 The m 6 A modification is recognized by its readers, YTH domain family proteins, amongst which YTHDF2 destabilizes m 6 Amodified mRNAs after binding within the consensus sequences. 2 A recent study reports that YTHDF2 deficiency results in female infertility in mice, and YTHDF2 is maternally required for oocyte maturation. 4 However, the physiological role of YTHDF2 in hematopoietic stem cell (HSC) biology was still unknown.…”
mentioning
confidence: 99%
“…1 Recent research has identified enzymes specifically involved in adjusting m 6 A methylation levels and their functional outcomes; this has been considered another layer of epigenetic control similar to DNA and histone modifications, and has increased our knowledge of epitranscriptomics. 2 The m 6 A methyltransferase complex, or the "writer", consists of Methyl transferase-like 3 and 14 (METTL3 and METTL14) with the cofactor Wilms tumor 1 associated protein (WTAP). METTL3 and METTL14 play critical roles in both normal hematopoiesis and leukemogenesis.…”
mentioning
confidence: 99%